Diet influenced tooth erosion prevalence in children and adolescents: Results of a meta-analysis and meta-regression. Issue 8 (August 2015) - Salas, M.M.S.; Nascimento, G.G.; Vargas-Ferreira, F.; Tarquinio, S.B.C.; Huysmans, M.C.D.N.J.M.; Demarco, F.F.
Abstract Objective The aim of the present study was to assess the influence of diet in tooth erosion presence in children and adolescents by meta-analysis and meta-regression. Data Two reviewers independently performed the selection process and the quality of studies was assessed. Sources Studies published until May 2014 were identified in electronic databases: Pubmed, EBSHost, Scopus, Science direct, Web of Science and Scielo, using keywords. Study selection Criteria used included: observational studies, tooth erosion and diet, subject age range 8–19 years old, permanent dentition and index. Meta-analysis was performed and in case of heterogeneity a random-effects model was used. Thirteen studies that fulfilled the inclusion criteria were selected. Higher consumption of carbonated drinks (p = 0.001) or acid snacks/sweets (p = 0.01 and for acid fruit juices (p = 0.03)) increased the odds for tooth erosion, while higher intake of milk (p = 0.028) and yogurt (p = 0.002) reduced the erosion occurrence. Heterogeneity was observed in soft drinks, confectionary and snacks and acidic fruit juices models. Methodological issues regarding the questionnaires administration and the inclusion of other variables, such as food groups and tooth brushing, explained partially the heterogeneity observed. Conclusions Some dietary components (carbonated drinks, acid snacks/sweets and natural acidic fruits juice) increased erosion occurrence while milk and yogurt had a protective effect. Methods to assess diet could influence the homogeneity of the studies and should be considered during the study design. Clinical significance The method to assess diet should be carefully considered and well conducted as part of the clinical assessment of tooth erosion, since diet could influence the occurrence of tooth erosion.